SCHOOL-BASED LITERACY PROGRAM TO IMPROVE STUDENTS READING COMPETENCIES IN EARLY YEARS OF PRIMARY EDUCATION IN RURAL AREAS - Wijaya, Adhimas Wahyu Agung (IJIET (International Journal of Indonesian Education and Teaching), 2025)
Improving literacy for early-grade children in primary schools in rural areas in Indonesia is a complex task due to the limited availability of reading resources and the varying teachers pedagogy competencies to teach students. This study aims to explore how school-based literacy programs by enhancing teachers teaching practices and improving the literacylearning environment at schools may improve students reading competencies, especially in lower grades. Using mixed methods, this study explains how studentsimprove theirreading competencies and this study also explores supporting factors and challenges to improve students' literacy. The sample of the study is 800 students and 92 teachers or principals in 28 primary schools in a district in West Kalimantan, Indonesia. The proportion of students who can read (categorized as a reader)improved after the program intervention. Several supporting factors that contribute to the improvement of student reading competencies have been identified such as teachers' motivation, teaching strategies, the availability of print-rich learning materials, and the support of school principals in literacy programs.